A Multicenter, Open-Label, Single-Arm Trial of the Efficacy and Safety of Empagliflozin Treatment for Refractory Diabetes Mellitus with Insulin Resistance (EMPIRE-01) - Hirota, Yushi; Kakei, Yasumasa; Imai, Junta; Katagiri, Hideki; Ebihara, Ken; Wada, Jun; Suzuki, Junichi; Urakami, Tatsuhiko; Omori, Takashi; Ogawa, Wataru (Diabetes therapy, 2024)
Introduction Insulin resistance syndrome and lipoatrophic diabetes are characterized by severe insulin resistance and are often refractory to treatment. Trials assessing the efficacy of antidiabetes drugs for these rare conditions have been limited, however. Sodium-glucose cotransporter 2 (SGLT2) inhibitors, which lower glycemia independently of insulin action, have shown efficacy for type 2 diabetes with insulin resistance. We here investigated the efficacy and safety of the SGLT2 inhibitor empagliflozin for treatment of insulin resistance syndrome and lipoatrophic diabetes. Methods The trial was conducted at five academic centers in Japan and included seven patients with insulin resistance syndrome and one patient with lipoatrophic diabetes. Participants received 10 mg of empagliflozin daily. If the hemoglobin A 1c (HbA 1c ) level was ≥ 7.0% (52 mmol/mol) after 12 weeks, the dose was adjusted to 25 mg. The study duration was 24 weeks, and the primary outcome was the change in HbA 1c level by the end of the treatment period. Safety evaluations were performed for all participants. Results By the end of the 24-week treatment period, the mean HbA 1c level for all eight patients had decreased by 0.99 percentage points (10.8 mmol/mol) (95% confidence interval [CI], 0.59 to 1.38 percentage points, 6.6 to 14.9 mmol/mol) and the mean fasting plasma glucose concentration had declined by 63.9 mg/dL (3.55 mmol/L) (95% CI 25.5 to 102.3 mg/dL, 1.42 to 5.68 mmol/L). Continuous glucose monitoring revealed a reduction in mean glucose levels from 164.3 ± 76.1 to 137.6 ± 46.6 mg/dL (9.13 ± 4.23 to 7.65 ± 2.59 mmol/L) as well as an increase in the time in range (70–180 mg/dL) from 58.9 ± 36.1% to 70.8 ± 18.3%. Seventeen mild adverse events were recorded in five individuals throughout the study period. No severe events were reported. The mean body mass showed a slight decrease and the mean serum ketone body concentration showed a slight increase during treatment. Conclusion Our results demonstrate that empagliflozin shows a certain level of efficacy and safety for treatment of insulin resistance syndrome and lipoatrophic diabetes. Trial Registration jRCTs2051190029 and NCT04018365.